PENERAPAN GREEN HUMAN RESOURCE MANAGEMENT DALAM EKOSISTEM KEWIRAUSAHAAN: SEBUAH SYSTEMATIC LITERATURE REVIEW (2019-2026) - Nadya Fitriana Tawary; Tri Siwi Agustina (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine the role of Green Human Resource Management (GHRM) in enhancing organizational sustainability through its influence on employee green behavior, eco-innovation, and environmental performance. It addresses a gap in the literature regarding the mechanisms linking GHRM practices to environmental outcomes, with particular emphasis on behavioral and organizational contextual factors. This research employs a systematic literature review approach using the PRISMA method, analyzing 38 relevant empirical studies. A systematic synthesis was conducted to identify patterns in the relationships among GHRM, employee green behavior, eco-innovation, and environmental performance across various organizational contexts. The findings reveal that GHRM has a strong impact on employee green behavior, which serves as a primary mediator in improving environmental performance, while eco-innovation acts as a complementary and context-dependent mechanism. This study offers novelty by demonstrating that the relationship between GHRM and environmental performance is non-linear, behavior-mediated, and context-dependent. These findings contribute to expanding theoretical perspectives and shifting the focus from policy-based approaches to behavior-based approaches in understanding organizational sustainability.